2014
DOI: 10.1007/s00392-014-0767-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in patients with cardiogenic shock complicating myocardial infarction: a substudy of the IABP-SHOCK II-trial

Abstract: In this large-scale multicenter study in patients with CS complicating AMI, women had a worse-risk profile in comparison to men. No significant gender-related differences in treatment as well as short- and long-term outcome were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 27 publications
4
26
2
1
Order By: Relevance
“…Consistent with our cohort, previous studies have also found women presenting with CS to be significantly older than men [ 12 , 16 , 17 , 18 , 19 , 22 ], however, the mean age of both groups in our study (76 years in women and 70.8 in men) were much higher than those already reported. Collado-Lledó et al reported mean ages of 67 and 64 years old for women and men, respectively [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our cohort, previous studies have also found women presenting with CS to be significantly older than men [ 12 , 16 , 17 , 18 , 19 , 22 ], however, the mean age of both groups in our study (76 years in women and 70.8 in men) were much higher than those already reported. Collado-Lledó et al reported mean ages of 67 and 64 years old for women and men, respectively [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Compared to men, women with AMI have a higher unadjusted mortality rate and lower use of guideline-recommended therapies, such as early intervention, reperfusion therapy, administration of thienopyridines, and glycoprotein inhibitors [ 13 , 14 , 15 ]. Moreover, gender-related management disparities have also been reported in the context of chronic heart failure [ 16 , 17 , 18 ] and cardiogenic shock [ 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few randomized trials [ 3 , 14 , 15 ] addressing patients with CS showed negative results, and literature is mostly base in heterogeneous observational studies addressing ACS-related CS [ 16 21 ]. The proportion of women in these series ranges between 25 and 45%, with mean ages ranging between 65 and 80 years [ 16 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 In the setting of CS, women have been shown to have a higher risk-factor profile and are less likely to be treated with intra-aortic balloon pump. 7,8 Despite the high prevalence of CS complicating AMI in women, there is a paucity of sex-specific safety, effectiveness, and outcomes data for mechanical support in the setting of CS, particularly prior to FDA approval. 9 The results of the USpella Registry, including results in patients with a confirmed AMI complicated by CS who underwent percutaneous coronary intervention (PCI) and were supported by an Impella 2.5 device (Abiomed, Danvers), have been previously published.…”
Section: Introductionmentioning
confidence: 99%